KOMUNIKASI INTERPERSONAL ANTARA ORANG TUA DAN ANAK DALAM MEMILIH STUDI LANJUT ( STUDI KASUS PADA SISWA GAP YEAR TAHUN 2022) - Dliyaussathi Nurmalita Azza; Desi Adissetianti Putri; Siti Andina Aisyah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
In decision-making involving parents and children, sometimes there are differences of opinion in it, especially to determine the future such as the level of education. To determine this level of education, the factor that sometimes becomes a dispute between parents and children is the orientation of the intended career path. For this problem, especially the determination to enter college, there are many obstacles for both. For this reason, this research was conducted to analyse the reasons for the difference of opinion for further study to college between children and parents. Therefore, the researcher has observed several gap year students in 2022 to be observed regarding their reasons for choosing a gap year and their parents' opinions on the reasons why they gap year.